The Relationship Between Waist Circumference, Wrist Circumference, and Body Mass Index in Carpal Tunnel Syndrome (Annals of Medical Research, 2021)
None
Keywords: Carpal Tunnel Syndrome; Body Mass Index; Wrist Circumference; Waist Circumference; Age.